1997
DOI: 10.1002/(sici)(1997)5:2<74::aid-nt4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid is a potent neurotoxin to neonatal rats

Abstract: Domoic acid induces a time‐dependent neuroexcitotoxic effect in neonatal rats characterized hyperactivity, stereotypic scratching, convulsions, and death with observable behaviors occurring at exposures 40 times lower by body weight in neonates than reported in adults. Low doses of domoic acid (0.1 mg/kg) induced c‐fos in the central nervous system which was inhibited in part by 2‐amino‐5‐phosphonovaleric acid, an NMDA receptor antagonist. Domoic acid caused no evidence of structural alteration in the brain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…Given the recognized neuroexcitatory effects of DA via glutamate receptors, the observed behavioral dysfunction is perhaps not surprising, however, specific mechanisms for these and other effects, particularly including morphological abnormalities, have not been clarified. That said, observed behavioral effects of DA in zebrafish embryos parallel those reported for rodent models (Xi et al, 1997;Doucette et al, 2000) that specifically indicate structural changes in the hippocampus of DA-exposed neonatal rats (Dakshinamurti et al, 1993).…”
Section: Freshwater Fish As Models For Developmental Toxins From Marisupporting
confidence: 66%
“…Given the recognized neuroexcitatory effects of DA via glutamate receptors, the observed behavioral dysfunction is perhaps not surprising, however, specific mechanisms for these and other effects, particularly including morphological abnormalities, have not been clarified. That said, observed behavioral effects of DA in zebrafish embryos parallel those reported for rodent models (Xi et al, 1997;Doucette et al, 2000) that specifically indicate structural changes in the hippocampus of DA-exposed neonatal rats (Dakshinamurti et al, 1993).…”
Section: Freshwater Fish As Models For Developmental Toxins From Marisupporting
confidence: 66%
“…[43][44][45] In the brain, induction of c-fos has been described as a marker of seizure activity and an early sign of neuronal excitotoxicity after exposure to glutamate, kainic acid, and DA. 33,46,47 Studies from Peng and Ramsdell 47 and Xi et al 48 showed that c-fos mRNA was induced in the brain at concentrations as low as 1.0 mg/kg DA (with nuclear immunolocalization at 0.5 mg/kg) in adult mice and as low as 0.1 mg/kg in neonates. Determining a lower limit of DA toxicity is essential to understanding the potential risks of exposure, although extrapolating results obtained in rodent studies to equivalent DA exposure levels in humans or other mammals is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Age and dose effects associated with domoic acid exposure have been demonstrated in humans, rats and monkeys, with adults being shown to be more susceptible to the toxin than juveniles (Scallet et al 1993;Truelove et al 1996). Additionally, both intrauterine and neonatal exposure in rats resulted in permanent behavioural and morphologic changes associated with reduced seizure threshold and decreased ability to perform memory tasks (Xi et al 1997;Doucette et al 2004). Morphologic changes included hippocampal neuronal loss and mossy fibre sprouting (indicative of new synapse formation) in the rat neonates and the authors hypothesize that this reorganization provided a substrate for hippocampal excitability, resulting in the observed behavioural changes.…”
Section: Discussionmentioning
confidence: 99%